Researching the stability of CaO from different precursors under varying absorption times - Plugge, Myron; Giammaria, Guido; Lefferts, Leon (Student Undergraduate Research E-journal!, 2015)
CaO was prepared from three different precursors (calcium carbonate, calcium L-ascorbate, calcium D-gluconate). The samples were calcined at four different temperatures (750 °C, 800 °C, 850 °C, 900 °C) and those with the highest internal surface area were chosen for use within the absorption/desorption cycle research. Of the synthetised samples the one prepared from calcium carbonate and calcined at 850 °C had the highest internal surface area (34,54 m2/g). Of the samples which underwent different adsorption cycles the ascorbate sample seemed to benefit most from shorter absorption cycles, increasing its projected long-term performance from 20,5% to an impressive 97,1%.